2022
DOI: 10.1021/acsami.1c20640
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Tracking of Temperature by Concurrent Periodic Precipitation Pattern Formation in Polyacrylamide Gels

Abstract: In nature, nonequilibrium systems reflect environmental changes, and these changes are often “recorded” in their solid body as they develop. Periodic precipitation patterns, aka Liesegang patterns (LPs), are visual sums of complex events in nonequilibrium reaction–diffusion processes. Here we aim to achieve an artificial system that “records” the temperature changes in the environment with the concurrent LP formation. We first illustrate the differences in 1-D LPs developing at different temperatures in terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 40 publications
3
23
0
Order By: Relevance
“…According to this behavior, LP could be employed for practical purposes to track the polarity changes in unknown solvents, similar to the use of LPs for tracking environmental changes. 15 , 16 , 30 Moreover, tuning the solvent polarity can be a promising strategy to control, tailor, and design both regular LPs and new hierarchical structures. In addition, hierarchical layered structures are of great importance for the design of self-organized functional materials from nano- to macroscale.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to this behavior, LP could be employed for practical purposes to track the polarity changes in unknown solvents, similar to the use of LPs for tracking environmental changes. 15 , 16 , 30 Moreover, tuning the solvent polarity can be a promising strategy to control, tailor, and design both regular LPs and new hierarchical structures. In addition, hierarchical layered structures are of great importance for the design of self-organized functional materials from nano- to macroscale.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this result, we constructed one possible model, and simulation using this model showed good qualitative agreement with experimental observations. According to this behavior, LP could be employed for practical purposes to track the polarity changes in unknown solvents, similar to the use of LPs for tracking environmental changes. ,, Moreover, tuning the solvent polarity can be a promising strategy to control, tailor, and design both regular LPs and new hierarchical structures. In addition, hierarchical layered structures are of great importance for the design of self-organized functional materials from nano- to macroscale. Some recent studies showed that LPs can be formed using some functional materials (e.g., metal nanoparticles and metal–organic frameworks), and another study indicated how to form microscale periodicity. ,,, By combining this knowledge with our strategy of polarity-based LP control, LP could be a potential candidate for the generation of self-organized hierarchical layered structures with various functions and structures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The formation of the periodic zone was apparent at [KI] above 0.1 M on the line profile. A further increase in [KI] moved the position of the periodic band farther away from the interface, which is a general feature of Liesegang pattern formation. Two empirical rules, namely, a spacing law and the Matalon–Packter law, can be used to confirm that the observed periodic band may be classified as a Liesegang band. The spacing law implies that the distance, x n , from the interface to the n th band obeys the following relationship (eq ): where n and p are the band number and spacing coefficient, respectively.…”
Section: Resultsmentioning
confidence: 99%